Diversifying Tasks in the English Language Classroom - Ramiaida Darmi; Fariza Puteh Behak; Yuslina Mohamed (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2016)
The use of tasks in the language classroom has been one of the current trends in language teaching. According to Edwards and Willis (2005), task-based language teaching (TBLT) provides contexts for activating learner acquisition processes and promotes second language (L2) learning. This paper reports a study that explores a diverse use of tasks in the English language classroom. The aim of the paper is to describe a task designed for low proficiency L2 learners’, and to explore learners’ task performance and their use of the L2 in the tasks. The study took place in a tertiary setting in Malaysia, and involved fourteen L2 learners. The task was designed based on Cummins’ (1981) framework, which focuses on the role of context and cognitive demands in language development. Learners’ worked in pairs, and were observed in the classroom. Each pair of learners’ discussions was audio-recorded, which were later analysed for their L2 use. Results indicated that learners’ L2 use increased when contextual support is high and cognitive demands is low. This suggests that designing tasks with higher order thinking is a challenge for teachers especially when it involves tertiary learners and requires learners to communicate more in their L2.